2000
DOI: 10.4049/jimmunol.164.1.223
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with Heat-KilledListeriaas Adjuvant Reverses Established Allergen-Induced Airway Hyperreactivity and Inflammation: Role of CD8+ T Cells and IL-18

Abstract: Asthma is a respiratory disorder characterized by airway hyperreactivity (AHR) and inflammation and is associated with high serum IgE and overproduction of IL-4, IL-5, and IL-13 by allergen-specific Th2 cells. Our previous studies demonstrated that heat-killed Listeria monocytogenes (HKL) as an adjuvant in immunotherapy successfully reversed ongoing Ag-specific Th2-dominated responses toward Th1-dominated responses, but it was unclear if such immune modulation could reverse ongoing, established disease in targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
2
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 54 publications
3
73
2
2
Order By: Relevance
“…The administration of various bacteria that can induce Th1-type immune responses has also been reported to inhibit the development of allergic-induced AHR. 40,41 These mechanisms have indirect inhibitory effects on the development of allergic AHR, since sensitization of hosts to a few species of bacteria, such as mycobacteria species, which can induce immune responses results in the elicitation of bacteria-specific Th1-type immune responses.…”
Section: Il-4 Antagonistic Mutant Dna Inhibits Allergic Airway Inflammentioning
confidence: 99%
“…The administration of various bacteria that can induce Th1-type immune responses has also been reported to inhibit the development of allergic-induced AHR. 40,41 These mechanisms have indirect inhibitory effects on the development of allergic AHR, since sensitization of hosts to a few species of bacteria, such as mycobacteria species, which can induce immune responses results in the elicitation of bacteria-specific Th1-type immune responses.…”
Section: Il-4 Antagonistic Mutant Dna Inhibits Allergic Airway Inflammentioning
confidence: 99%
“…6 Many subsequent studies also showed supportive data for the importance of immune deviation in the prevention of allergy. 19,20,[24][25][26] Immune regulation Although the relationship between the Th1-promoting effects of infections and the consequent inhibition of allergy provides an explanation for the hygiene hypothesis, the mechanism has been challenged because some Th1-type autoimmune diseases have also increased over the past decades. Moreover, some pro-Th2 parasitic infections were found to also inhibit allergic diseases.…”
Section: Immune Deviationmentioning
confidence: 99%
“…19,20 Some studies showed that systemic or mucosal administration of killed bacteria, introduction of bacterial CpG, and intramuscular infection with adenovirus also inhibit allergic reactions. [21][22][23][24][25][26] We have shown that the Chlamydia trachomatis mouse pneumonitis strain, more recently called C. muridarum, and BCG infections have a significant imprinting effect on newborn or young adult C57BL/6 and Balb/c mice; the imprinting inhibited allergy/asthma induced by natural or model allergens later in life. [31][32][33][34][35][36][37][38] In particular, C. muridarum infection had a strong imprinting effect on the inhibition of allergy, even after the infection had long been cleared.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were bled, and serum levels of OVA-specific IgG1, IgG2a, and IgE Abs were measured using modified OVA-specific ELISAs as previously described (17). Anti-OVA IgG1 and IgG2a mAbs 6C1 and 3A11, respectively, were used as standards for the quantification of each IgG subclass.…”
Section: Ova-specific Igs Assaymentioning
confidence: 99%